Utilization of Palm Fiber King as a Strengthening Material on Biocomposite - Gerald A Pohan; Totok Sugiarto; Dwi Cahyo Galih Arianto (Widyagama University of Malang, 2018)
Royal palm (Roystonea regia) is still utilized in traditional way. In this study, royal palm fiber is employed as a reinforcing material in composites. The fiber is divided into two groups of fibers, which are continuous and discontinuous, with a length of fibers of 20 and 5 cm, respectively. Continuous fibers are arranged in parallel, while discontinuous fibers are sown in random orientation. The variations in fiber volume fraction were 15, 25, 50, and 75%. Tensile tests were performed to determine composite strength. The test results show that composite tensile strength values with continuous fibers are higher than those of discontinuous fibers. In addition, the increase in fiber volume fraction is directly proportional to the tensile strength of the specimen. These results indicate that the royal palm fiber has the potential to be used in composite applications.Keywords: royal palm fiber, biocomposite, tensile strength